2021
DOI: 10.1515/tjb-2020-0624
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biochemical and immunological biomarker levels of patients with COVID-19 with healthy individuals

Abstract: Objectives It was aimed to compare Alpha-1 antitrypsin (AAT), Alpha-1 acid glycoprotein (AGP), Total Immunoglobulin M (Total IgM), Total Immunoglobulin G (Total IgG), Galectin-3 (Gal3), and severe acute respiratory syndrome coronavirus 2 IgG (SARS-CoV-2 IgG) levels in patients with COVID-19 and healthy individuals. Methods The study included a total of 86 participants, 44 patients diagnosed with COVID-19 by real-time reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…After removing Karsli et al (33), no change was observed in the significance of the results (SMD 0.69, 95% CI 0.44 to 0.94, P < 0.01, Figure 3), although heterogeneity was reduced to 60.42%. Removing five of the studies made the overall result insignificant (21,22,27,31,32).…”
Section: Gal-3 and Covid-19 331 Meta-analysis Of Gal-3 Levels In Covi...mentioning
confidence: 99%
See 1 more Smart Citation
“…After removing Karsli et al (33), no change was observed in the significance of the results (SMD 0.69, 95% CI 0.44 to 0.94, P < 0.01, Figure 3), although heterogeneity was reduced to 60.42%. Removing five of the studies made the overall result insignificant (21,22,27,31,32).…”
Section: Gal-3 and Covid-19 331 Meta-analysis Of Gal-3 Levels In Covi...mentioning
confidence: 99%
“…After removing duplicates, 524 records were screened by titles and abstracts. Following this step, 63 studies were evaluated by full texts, resulting in 18 final included studies (7,(19)(20)(21)(22)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). The PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) flow chart summarizing the selection process is available in Figure 1.…”
Section: Literature Search and Baseline Characteristics Of Included S...mentioning
confidence: 99%
“…Ercin et al (2021), which included 86 participants, 44 patients diagnosed with COVID-19 and 42 as the control group, revealed that patients with COVID-19 infection demonstrated a significant increase in AAT threshold, which is a great predictor for disease termination 41. IL-6 is a crucial modulator of the inflammatory and immunological response to infection or trauma.…”
mentioning
confidence: 99%